The evolution of polycentric governance in the galapagos small-scale fishing sector - Cáceres, R., Pittman, J., Castrejón, M.; Deadman, P. (My University, 2022)
Addressing the multiple anthropogenic and non-anthropogenic factors affecting small-scale fisheries requires collaboration from diverse regions, geographical scales, and administrative levels in order to prevent a potential misfit between governance systems and the socio-ecological problems they address. While connecting actors and stakeholders is challenging, as they often hold opposing perceptions and goals, unveiling the network configurations of governance systems remains one effective way to explore collaborative alliances in light of the diverse drivers of change present in small-scale fishery systems. This study employed descriptive statistics, exponential random graph models (ERGMs), and qualitative data analysis to explore preferential attachments of new nodes to well-positioned nodes within the Galapagos small-scale fishery governance system network and the propensity of cross-sectoral reciprocity and cross-sectoral open triads formation in the network. Our findings identified significant players and network configurations that might be essential in the collaboration diffusion and robustness of the Galapagos small-scale fishery sector governance system.
Keywords: Collaboration; Social network analysis; Small-scale fisheries